Scada ODL flipped classroom: a case study for the school of electrical engineering / Mahanijah Md Kamal and Noorfadzli Abd Razak - Md Kamal, Mahanijah; Abd Razak, Noorfadzli (Universiti Teknologi MARA, 2023)
Using open and distance learning (ODL) for courses that included laboratory sessions was challenging to teach and learn during the COVID-19 era. SCADA (Supervisory Control and Data Acquisition), also known as ESE691, is the School of Electrical Engineering elective that requires students to be present in the lab for their mini-project group assignments. During the outbreak, students were not permitted to attend the laboratory, but they were required to complete their assignments. The rapid transition from face-to-face delivery modalities to a flipped classroom will be more difficult for final-year electrical engineering students. As a result, the purpose of this study was to investigate the perceptions of students taking ESE691 in a flipped classroom environment from October 2020 to February 2021. The data was gathered using a qualitative method, and the results were analysed using SPSS. This survey had 68 participants, with 22 female students and 46 male students filling out a google form. The findings show that while using the ODL platform to create a flipped classroom for SCADA, the eight questions are critical. The implementation of the flipped classroom for the internal consistency test.